Rainwater harvesting potential in a semiarid Southern California city. Issue 1 (19th February 2019) - Summerville, Nathaniel; Sultana, Rebeka
Abstract : To determine the rainwater capture potential in a small residential city located in semiarid Southern California, a model of the city's existing storm drainage system was developed using a watershed management model based on the U.S. Environmental Protection Agency's storm water management model. The model analyzes the effect of (1) 2‐ and 10‐year 24‐h storms and (2) dry, average, and wet climatic conditions under five different scenarios, considering (1) single rain barrel, (2) 5 rain barrels, (3) 7 rain barrels, (4) 10 rain barrels, and (5) a storage tank in each residential lot. Results show that, due to its fixed capacity, rain barrel(s) can only save a limited amount of water. A storage tank per lot increases rainwater capture efficiency, which can collect 19% of city's annual reclaimed water volume in an average climatic year. However, storage tanks can only be cost‐effective to residents through financial supports from local agencies.